Carbon-free dry reforming of methane to syngas over NdCoO3 perovskite-type mixed metal oxide catalyst - Choudhary, Vasant R.; Mondal, Kartick C.; Mamman, Ajit Singh; Joshi, Upendra A. (Catalysis Letters, 2005)
CoNdOx (Co/Nd = 1) is a highly promising catalyst for the carbon-free CO2 reforming of methane. Influence of the Co/Nd ratio on the catalyst performance in the CO2 reforming and also on the crystalline phases and reduction by temperature programmed reduction (TPR) of the CoNdOx catalyst has also been investigated. The CoNdOx (CoNd = 1.0) catalyst consisted of mainly NdCoO3 perovskite- type mixed metal oxide and it showed not only a high resistance to carbon formation at different process conditions ( viz. temperature = 750 - 900 degrees C and gas hourly space velocity (GHSV) = 10000 - 50000 cm(3) g(-1) h(-1)) but also high activity and selectivity in the CO2 reforming process. The high resistance to carbon formation for this catalyst is attributed mostly to strong metal (Co degrees) - support (Nd2O3) interactions.
Keywords: CO2 reforming of methane to syngas; CoNdOx catalyst; NdCoO3 perovskite; resistance to carbon formation in CO2 reforming